Determinants of pentavalent and measles vaccination dropouts among children aged 12-23 months in The Gambia - Peter A. M. Ntenda; Alick Sixpence; Tisungane E. Mwenyenkulu; Kondwani Mmanga; Angeziwa C. Chirambo; Andy Bauleni; Owen Nkoka (BMC, 2022)
Abstract Background Every year, vaccination averts about 3 million deaths from vaccine-preventable diseases (VPDs). However, despite that immunization coverage is increasing globally, many children in developing countries are still dropping out of vaccination. Thus, the present study aimed to identify determinants of vaccination dropouts among children aged 12-23 months in The Gambia. Methods The study utilized cross-sectional data obtained from the Gambia Demographic and Health Survey 2019-20 (GDHS). The percentage of children aged 12-23 months who dropped out from pentavalent and measles vaccination were calculated by (1) subtracting the third dose of pentavalent vaccine from the first dose of Pentavalent vaccine, and (2) subtracting the first dose of measles vaccine from the first dose Pentavalent vaccine. Generalized Estimating Equation models (GEE) were constructed to examine the risk factors of pentavalent and measles vaccinations dropout. Results Approximately 7.0% and 4.0% of the 1,302 children aged 12-23 months had dropped out of measles and pentavalent vaccination respectively. The multivariate analyses showed that when caregivers attended fewer than four antenatal care sessions, when children had no health card or whose card was lost, and resided in urban areas increased the odds of pentavalent dropout. On the other hand, when women gave birth in home and other places, when children had no health card, and being an urban areas dweller increased the odds of measles dropout. Conclusion Tailored public health interventions towards urban residence and health education for all women during ANC are hereby recommended.